Mental Health in Cases of Teenage Suicide - Hanifah Hikmawati; Miftakul Nurul Kasanah (CV Kalimasada Group, 2025)
: This study examines the phenomenon of suicide among university students and adolescents from diverse backgrounds, emphasizing the relationship between mental health conditions and suicidal behavior. The research aims to identify key psychological, social, and emotional factors contributing to suicidal tendencies in youth. Using a qualitative approach supported by case study analysis, the data were obtained through documentation review and interviews with mental health professionals. The findings reveal that most victims exhibited symptoms of mental health disorders, including inner conflict, communication difficulties, and self-harm ideation, which significantly impaired their social functioning and emotional stability. Furthermore, these conditions often manifested in mood fluctuations and deteriorating physical well-being. The study concludes that early detection of mental health disorders and the provision of continuous social and emotional support are essential strategies to prevent adolescent suicide. These findings highlight the need for collaborative interventions between educational institutions, families, and healthcare providers to promote mental well-being and resilience among adolescents.